2018
DOI: 10.1038/s41401-018-0044-4
|View full text |Cite
|
Sign up to set email alerts
|

PARP1 interacts with HMGB1 and promotes its nuclear export in pathological myocardial hypertrophy

Abstract: High-mobility group box 1 (HMGB1) exhibits various functions according to its subcellular location, which is finely conditioned by diverse post-translational modifications, such as acetylation. The nuclear HMGB1 may prevent from cardiac hypertrophy, whereas its exogenous protein is proven to induce hypertrophic response. This present study sought to investigate the regulatory relationships between poly(ADP-ribose) polymerase 1 (PARP1) and HMGB1 in the process of pathological myocardial hypertrophy. Primary-cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Recent evidence has suggested that PARP1 facilitated LPS‐induced HMGB1 release via acetylation modification 26,27 . Besides, the interaction between PARP1 and HMGB1 proteins has also been reported 28,29 …”
Section: Introductionmentioning
confidence: 96%
“…Recent evidence has suggested that PARP1 facilitated LPS‐induced HMGB1 release via acetylation modification 26,27 . Besides, the interaction between PARP1 and HMGB1 proteins has also been reported 28,29 …”
Section: Introductionmentioning
confidence: 96%
“…5-BrdU (Beijing Solarbio Science & Technology Co., Ltd.) was added to a final concentration of 0.1 mmol/l to prevent the growth of fibroblasts, and the cells were further cultured in an incubator. According to previous studies (20)(21)(22)(23)(24) ) was used as the secondary antibody and incubated with the membrane at 4˚C for 2 h. The results were detected with enhanced chemiluminescence reagents (Wanleibio Co., Ltd.). Finally, membranes were scanned using a Bio-Rad image analyzer; and densitometry analysis was performed using Quantity One version 4.4 (Bio-Rad Laboratories, Inc.).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the effects of the ERK1/2 signaling pathway on the manner by which AA attenuates PCAF mediated-H3K9ac hyperacetylation in PE-induced hypertrophic cardiomyocytes was determined. First, according to the previous literature (21)(22)(23)(24), the optimum concentration of the histone acetylase inhibitor AA was determined (50 µmol/l), as well as for the ERK inhibitor U0126 (10 µmol/l), in accordance with H3K9ac levels, and the viability of myocardial cells using western blotting and CCK-8 examination, respectively (Fig. 2A and B).…”
Section: P-erk1/2 Interacts With Pcaf and Altered H3k9ac Acetylation In Hypertrophic Cardiomyocytes Induced By Pementioning
confidence: 99%
“…PARP1, a member of PARP enzyme family, can modulate diverse biological processes through covalent transfer of ADP-ribose from NAD + onto substrate proteins or DNA chain, known as poly(ADP-ribosyl)ation (PARylation) 21 , 22 , 23 . Our previous studies have revealed that PARP1 is activated and PARylates FOXO3, STAT3 and HMGB1 in cardiac hypertrophy, whereas inhibition of PARP1 by 3-aminobenzamide (3AB) and veliparib (ABT-888) prevents the development of cardiac hypertrophy 24 , 25 , 26 , 27 . The observations of BRD4/PARP1 interaction thus prompt our hypothesis that BRD4 might act as a substrate protein of PARP1, and that PARylation of BRD4 by PARP1 might facilitate the recruitment of BRD4 to hyper-acetylated chromatin and enhance RNA Pol II phosphorylation, ultimately promoting transcription activation of hypertrophic biomarkers.…”
Section: Introductionmentioning
confidence: 99%